2009
DOI: 10.1002/term.191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agarose mould compliance and surface roughness on self-assembled meniscus-shaped constructs

Abstract: The meniscus is a fibrocartilaginous tissue that is critically important to the loading patterns within the knee joint. If the meniscus structure is compromised, there is little chance of healing due to limited vascularity in the inner portions of the tissue. Several tissue engineering techniques to mimic the complex geometry of the meniscus have been employed. Of these, a self-assembly, scaffoldless approach employing agarose molds avoids drawbacks associated with scaffold use while still allowing formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Primary meniscus cells are often used for this purpose, and have shown great promise in creating tissue engineered constructs with properties similar to native cartilage. [1][2][3][4][5][6][7][8] To obtain meniscus cells for tissue engineering efforts, enzymatic digestion is needed, but little is known about the effects of isolation on the phenotype of meniscus cells, or which digestion technique is most effective for extracting cells from the meniscus. Isolating cells from fibrocartilaginous tissues such as the meniscus is difficult due to the abundance of fibrous extracellular matrix (ECM).…”
mentioning
confidence: 99%
“…Primary meniscus cells are often used for this purpose, and have shown great promise in creating tissue engineered constructs with properties similar to native cartilage. [1][2][3][4][5][6][7][8] To obtain meniscus cells for tissue engineering efforts, enzymatic digestion is needed, but little is known about the effects of isolation on the phenotype of meniscus cells, or which digestion technique is most effective for extracting cells from the meniscus. Isolating cells from fibrocartilaginous tissues such as the meniscus is difficult due to the abundance of fibrous extracellular matrix (ECM).…”
mentioning
confidence: 99%
“…[40][41][42] At the same time, 3D woven PCL scaffolds have conferred increased biomechanical properties in a composite preparation with cartilage-derived matrix, obviating the need for growth factor augmentation, and may certainly be applied to meniscus restoration. 43,44 Gunja et al [45][46][47][48] have conducted work using nonwoven poly-L-lactic acid scaffolds exploring the positive synergistic effects of bFGF and hypoxia, hydrostatic pressure, and TGF-ß and coculture (chondrocytes and meniscus cells) using in vitro models. Ultimately, it is hoped that cellular infiltration and matrix deposition may restore some of the viscoelastic properties of meniscus tissue in which the fluid phase carries a significant amount of the load.…”
Section: Biological Augmentation and Tissue Engineering Approaches Inmentioning
confidence: 99%
“…24,25 An additional positive die representing the inner one-third of the rabbit meniscus was similarly created. The positive die was plunged into molten 2% agarose (Fisher Scientific), and the agarose was allowed to set.…”
Section: Mold Fabricationmentioning
confidence: 99%
“…Previous work has shown that this ratio of cells yields constructs with both collagen types I and II, consistent with the fibrocartilage matrix content. 25,27,28 These cells were seeded into the meniscus-shaped agarose wells. After 7d, the intact control meniscus constructs were removed from the wells and placed into plastic six-well plates (BD Biosciences) coated with 2% agarose to prevent construct adhesion, cell migration, and construct deformation through outgrowth of their meniscus-shaped wells.…”
Section: Control 50:50 Meniscus Constructsmentioning
confidence: 99%